Carbon emission analysis and evaluation of industrial departments in China: An improved environmental DEA cross model based on information entropy. (1st January 2018) - Han, Yongming; Long, Chang; Geng, Zhiqiang; Zhang, Keyu
Abstract: Environmental protection and carbon emission reduction play a crucial role in the sustainable development procedure. However, the environmental efficiency analysis and evaluation based on the traditional data envelopment analysis (DEA) cross model is subjective and inaccurate, because all elements in a column or a row of the cross evaluation matrix (CEM) in the traditional DEA cross model are given the same weight. Therefore, this paper proposes an improved environmental DEA cross model based on the information entropy to analyze and evaluate the carbon emission of industrial departments in China. The information entropy is applied to build the entropy distance based on the turbulence of the whole system, and calculate the weights in the CEM of the environmental DEA cross model in a dynamic way. The theoretical results show that the new weight constructed based on the information entropy is unique and optimal globally by using the Monte Carlo simulation. Finally, compared with the traditional environmental DEA and DEA cross model, the improved environmental DEA cross model has a better efficiency discrimination ability based on the data of industrial departments in China. Moreover, the proposed model can obtain the potential of carbon emission reduction of industrial departments to improve the energy efficiency. Graphical abstract: Highlights: An improved environment DEA cross model method is proposed. Environment efficiency analysis and evaluation framework of industrial departments is obtained. This proposed method is efficient in carbon emission reduction of industrial departments in China.